2011
DOI: 10.1016/j.ajpath.2011.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Selective Regulation of Cardiac Organic Cation Transporter Novel Type 2 (OCTN2) in Dilated Cardiomyopathy

Abstract: Organic cation transporters (OCT1-3 and OCTN1/2) facilitate cardiac uptake of endogenous compounds and numerous drugs. Genetic variants of OCTN2, for example, reduce uptake of carnitine, leading to heart failure. Whether expression and function of OCTs and OCTNs are altered by disease has not been explored in detail. We therefore studied cardiac expression, heart failure-dependent regulation, and affinity to cardiovascular drugs of these transporters. Cardiac transporter mRNA levels were OCTN2>OCT3>OCTN1>OCT1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 62 publications
(60 reference statements)
3
42
0
Order By: Relevance
“…21 This mechanism deserves further investigation, given the known association of primary carnitine deficiency due to mutations in the OCTN2 gene with cardiomyopathic failure 22 and the reduced expression of OCTN2 in endomyocardial biopsy specimens of patients with chronic DCM. 23 Our results were unequivocal in identifying marked and consistent reductions in myocardial acylcarnitines in advanced HF across a broad spectrum of carbon chain lengths (Figure 2B, Supplemental Figure 2). Transgenic models with impaired FAO such as the LCAD deficient and PPARα knock out mice have each demonstrated increased accumulation of long-chain acylcarnitines in the myocardium.…”
Section: Discussionsupporting
confidence: 61%
“…21 This mechanism deserves further investigation, given the known association of primary carnitine deficiency due to mutations in the OCTN2 gene with cardiomyopathic failure 22 and the reduced expression of OCTN2 in endomyocardial biopsy specimens of patients with chronic DCM. 23 Our results were unequivocal in identifying marked and consistent reductions in myocardial acylcarnitines in advanced HF across a broad spectrum of carbon chain lengths (Figure 2B, Supplemental Figure 2). Transgenic models with impaired FAO such as the LCAD deficient and PPARα knock out mice have each demonstrated increased accumulation of long-chain acylcarnitines in the myocardium.…”
Section: Discussionsupporting
confidence: 61%
“…Although neural norepinephrine uptake-1 is the major mechanism of norepinephrine handling in nerve terminals reflecting sympathetic nerve activity, the nonneural uptake-2 mechanism also contributes to the removal of norepinephrine from the synaptic cleft and changes in pathologic conditions (12,16,18). Recently, it has been suggested that the nonneural uptake-2 mechanism is involved in provoking arrhythmias and in the progression of heart failure (16,(18)(19)(20). Therefore, these results imply that 18 F-LMI1195 has the potential to be a new class of assay to facilitate research into the understanding of cardiac norepinephrine uptake-2 mechanism in various heart diseases and might be used for monitoring the effects of medication on the norepinephrine uptake in rat models.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that increased circulating levels of TNF-and IL-6 in patients with congestive heart failure were inversely proportional to CYP2C19 and CYP1A2 activity (Frye et al, 2002). Similarly, downregulation of OCTN2 expression in patients with dilated cardiomyopathy inversely correlated with cardiac CD3 + T-cell count (Grube et al, 2011). In addition, cardiac cytokine release may affect OCTN2 expression during cardiomyopathy associated with inflammation.…”
Section: Mechanisms Of Altered Drug Metabolism In Cvdsmentioning
confidence: 96%
“…A recent study demonstrated a selective disease-dependent regulation of the high-affinity carnitine transporter, OCTN2, in patients with dilated cardiomyopathy, whereas the other OCT(N)s were unaffected (Grube et al, 2011).…”
Section: Drug Transportersmentioning
confidence: 99%